Right of petition and administrative silence - Fernández Ruiz, Jorge (2020)
With unfortunate frequency, public officials in charge of the exercise of public power ignore the requests of the governed for refraining from responding to them, in clear violation of their right to petition and of their fundamental right to good public administration, unlawful only aggravates the particular interest of the applicant, but its impunity undermines the basis of the rule of law, so it is necessary to reform the current regulations in order to toughen the sanctions to public officials who incur in such misconduct to the detriment of the petitioner, which the legislator has tried to mitigate through the figure of administrative silence.